Clerodane diterpenes: sources, structures, and biological activities - Li, Rongtao; Morris-Natschke, Susan L; Lee, Kuo-Hsiung (Natural product reports, 2016)
Covering: 1990 to 2015 The clerodane diterpenoids are a widespread class of secondary metabolites and have been found in several hundreds of plant species from various families and in organisms from other taxonomic groups. These substances have attracted interest in recent years due to their notable biological activities, particularly insect antifeedant properties. In addition, the major active clerodanes of Salvia divinorum can be used as novel opioid receptor probes, allowing greater insight into opioid receptor-mediated phenomena, as well as opening additional areas for chemical investigation. This article provides extensive coverage of naturally occurring clerodane diterpenes discovered from 1990 until 2015, and follows up on the 1992 review by Merritt and Ley in this same journal. The distribution, chemotaxonomic significance, chemical structures, and biological activities of clerodane diterpenes are summarized. In the cases where sufficient information is available, structure activity relationship (SAR) correlations and mode of action of active clerodanes have been presented. The clerodane diterpenoids are a widespread class of secondary metabolites and have been found in several hundreds of plant species from various families and in organisms from other taxonomic groups.